Pembelajaran Bahasa Arab Ramah Anak untuk Anak Usia Infancy - M. Mansyur; Maltuful anam (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
This study aims to find out how Child-Friendly Arabic Learning is Implemented in Early Childhood Children who are in the Infancy Stage at the Ummul Quro Pamekasan Early Childhood Education Institute. The researcher used a descriptive qualitative approach with the type of research being phenomenological with three data collection techniques namely interviews, observation and documentation. While data analysis uses several stages, namely data collection, data reduction, data presentation and drawing conclusions. The findings in this study indicate that the implementation of child-friendly Arabic language learning for infancy stage children in Ummul quro early childhood education (PAUD) is carried out in several stages as follows, namely First, the planning stage. Second, Implementation Stage and Third, Evaluation Stage.